University entrepreneurial support and green entrepreneurial behavior: a quantitative serial mediation - Nimit Soonsan; Hiran Prasankarn; Piangjit Tanticharatwarodom; Jiraporn Prasankarn; Zulfiqar Ali Jumani (Journal of Innovation and Entrepreneurship)
Abstract This study aims to delineate the influence of university support for entrepreneurship on fostering green entrepreneurial behaviours, specifically examining the roles of entrepreneurial self-efficacy and green entrepreneurial intention as sequential mediators in this relationship. Employing a quantitative methodology, data from 338 Thai entrepreneurs were collected through a structured survey using convenience sampling techniques. The analysis reveals that university support positively influences green entrepreneurial behaviors. Specifically, university support positively increases entrepreneurial self-efficacy, which, in turn, positively influences green entrepreneurial intentions. This sequential mediation demonstrates that the positive relationship between university support and green entrepreneurial behaviors is enhanced by the mediating roles of entrepreneurial self-efficacy and green entrepreneurial intentions. This underscores the critical role of universities in boosting self-efficacy among budding entrepreneurs and cultivating their green intentions, which are essential for sustainable entrepreneurial practices. This study is an exploratory step in understanding university support and green entrepreneurship dynamics. Future research could incorporate longitudinal data collection to establish causality more definitively and include industry-specific factors (e.g., regulatory frameworks, market demand for green products) and the economic climate (e.g., access to green financing, government incentives) to provide a more nuanced understanding of this relationship. Furthermore, future studies should employ probability sampling methods, such as stratified random sampling, to enhance the generalizability of the findings to a broader population of entrepreneurs. This research pioneers in illustrating the interconnected pathways through which university support can translate into green entrepreneurial actions. By integrating serial mediation analysis, this study offers new insights into the sequential impacts of university support on entrepreneurial self-efficacy and intention, highlighting their importance in fostering sustainable entrepreneurial outcomes.